(untitled) (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2020)
The muddy beach vulnerable to wave damage, coastal protection is needed by using permeable breakwaters type. Permeable breakwaters are being developed, namely with Pile Breakwater. The material used for the protoype in laboratory is rounded insulated bamboo, which is round bamboo from Pringgodani garden with a diameter of 1 cm, height of 20 cm with a multiblock wooden bulkhead with thick of 2 cm. Reflection and transmission analysis on the results of 2D physical modelling of the breakwater is needed to achieve optimization in its use. Breakwater is effective in scenarios that have smaller Kt values and larger Kr values. In this study the test was carried out with water level at Mean Sea Level (MSL) (44 cm) and High Water Level (HWL) (50 cm) with 2 spatial scenarios between 1 cm and 2 cm. Then the calculation results of Kt and Kr are compared with nondimensional wave steepness variables (Hi/gT2 ) and wave slope (Hi/L)). From this laboratory study, it is shown that has lower values at MSL and has higher values at MSL. This fact shows that the permeable breakwater with bamboo more effective at low water level than at high water level.